Extracorporeal Shock Wave Lithotripsy (ESWL): An Evaluation of Success in Low, Medium and High Stone Density - Rizwan Hussain, Humayun Saeed, Sana Rizwan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find the frequency of patients of renal calculi with different stone densities and to evaluate the success rate of ESWL treatment in selected groups of patients i.e. low, medium and high stone density. Methodology: In this descriptive case series, at Department of Urology, Services Hospital, Lahore was conducted and enrolled a 100 cases with single, radiopaque renal stone of 1-2 cm (10 to 20 mm), between 15-80 years of either gender whereas those with calculus in nonfunctioning kidney (GFR less than 15 ml/min), calculus in Pyonephrotic kidney, presence of JJ stent and having previous surgery for stone on same side or radiolucent stones were excluded from this study. All sessions of ESWL were performed following departmental protocol. 3 weeks after the ESWL session, the outcome was evaluated by plain X-ray KUB and USG KUB. In this analysis, ESWL success was defined as either total stone clearance or the presence of clinically insignificant residual fragments (CIRFs) (4 mm, peripheral, not producing renal colic, with no infection or extensive hematuria). Results: Stone density was in the range of 335-1900 HU with a mean density of 851.1 (±418) HU. Patients with medium density group (500-1000HU) were significantly greater than other two groups. MDG had frequency of 51% followed by LDG (25%) and HDG (24%). Overall, ESWL success rate was 82% in all the 100 patients of renal calculi. Success rate was greatest in LDG i.e. 100%. MDG had a success rate of 90% and only 45.8% of the patients in HDG had succees after ESWL treatment. Success rate decreased as the stone density increased. Conclusion: the stone density has a significant impact on success of ESWL. NCCT stone characteristics like mean density in HU and demographic characteristics are potential predictors for evaluation of success of ESWL. Keywords: Kidney stones, ESWL, Stone density